Independent Learning and Student Learning Responsibilities Characteristics of Mathematics Knowledge Competence in Fifth-Grade Elementary School - I Gusti Ayu Putu Putri Widayanti; Gusti Ngurah Sastra Agustika (Universitas Pendidikan Ganesha, 2023)
The habit of students procrastinating on assignments given by the teacher is one of the habits that need to be eliminated. It happened because of the need for more confidence in students in their abilities. This study aims to analyze the influence of independent learning and the character of students' learning responsibility on the competence of mathematics knowledge of fifth-grade elementary school students. This type of research is ex-post facto with a correlational research design. The population used in this study amounted to 116 students. Sampling is based on the existing population using a proportional random sampling technique to obtain a total sample of 92 people. The data was collected using a questionnaire instrument and document recording methods. The statistical analysis used is simple regression analysis and multiple regression analysis. The simple linear regression analysis results for testing hypotheses I and II show a significant effect of learning independence on the competency of mathematical knowledge and a significant effect of the character of learning responsibility on the competence of mathematical knowledge. The multiple linear regression analysis results showed a significant effect of learning independence and the character of student learning responsibility on the competence of mathematics knowledge of fifth-grade students in elementary school. It was concluded that there was a significant influence of learning independence and the character of students' learning responsibility on the competence of mathematics knowledge of fifth-grade elementary school students.